Education and cultural freedom: open pathway towards a plural state - Liliana Valladares Riveroll (Universidad Politécnica Salesiana, 2014)
In this paper it is argued that cultural freedom in education is a necessary condition to build a plural state. It proposes that to be truly intercultural and bilingual institution, education should ensure conditions for people to exercise their freedom to choose their cultural identity and live the life they have reason to value without being discriminated against or excluded thereby. Multiculturalism in education means that the values , knowledge, procedures and lifestyles of the diverse cultural groups that make up a society should be reflected not only in the curricula and in educational approaches, but also in the teacher education, pedagogical methods, and learning materials.